The role of auditor opinion in moderating the effect of financial distress on auditor switching in the infrastructure, utility, and transportation sub-sectors - Dedi Heru Prihandoko; Supriyati Supriyati (Universitas Hayam Wuruk Perbanas, 2020)
The purpose of this study is to analyze the effect of company growth and financial distress on auditor switching with going concern audit opinion as a moderating variable. The data used in this research are secondary data obtained from Indonesia Stock Exchange. The sample used in this study is 25 infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange (IDX). The study period is 5 years (2013-2017). Sampling in this study is conducted using purposive sampling method. The analysis techniques used are descriptive analysis, logistic regression, and moderated regression analysis. The dependent variable used is auditor switching, while the independent variables are company growth and financial distress, with going concernÂ audit opinion as the moderating variable.Â The results show that company growth has no effect on auditor switching, financial distress has an effect on Auditor switching, going concern audit opinion has no affect and cannot moderate the effect of company growth on auditor switching, going concern audit opinion has an effect but cannot moderate the effect of financial distress on auditor switching.